Bro, en senglacial boplads på Fyn - Andersen, Søren H. (Kuml, 1972)
Bro. A late glacial settlement of northern Funen The material illustrating late glacial culture in Denmark has long been based mainly on single finds. In recent years, however, new settlements have been discovered, and among these is the newly excavated site at Bro in northern Funen, fig. 4, the first settlement of its kind west of the Great Belt. The Bro settlement was discovered in late 1970, when two typical late glacial tanged points, fig. 1-2, and a dihedral burin, fig. 3, were found on the surface. In the following year the whole site was systematically excavated. Topography The settlement occupies a narrow terrace halfway down the steep southern face of a 14.3 m high hill of moraine clay, at the foot of which there is a small basin -a dead-ice hole, fig. 6. The moraine forms the northern end of an approximately 2 km long and 1 km wide depression, which in late glacial times was presumably a large lake, fig. 5. Excavation The majority of finds were made within an area measuring 10 x 13 m. The total excavated area, which may be regarded as the total extent of the settlement, was 61 sq. m, fig. 9. Stratigraphy Section QV, fig. 7, which cuts the excavation in an approximately east-west direction, illustrates the stratigraphy. The 20-30 cm thick topsoil loam covers a 40 cm thick layer of sand superjacent to moraine clay subsoil. The sand is a fine, well-sorted primary deposit containing large quantities of flint implements and flint waste, and was formed in water, presumably near the shore of a large lake. No charcoal, burnt bone or other organic material was found. A stone-lined fire place and burnt flint waste shows, however, that fire was used in the settlement, fig. 9. The excavation yielded large quantities of flint from both topsoil and underlying sand. The frequent occurrence of pieces of the same tool, broken in antiquity, in the sand and the topsoil respectively, demonstrates that topsoil finds originally derive from the sand. The distribution plan for flint waste, fig. 10-11, shows that the settlement area is well defined to the north, south and west, whilst it is more diffuse to the east and north-east. In both the topsoil and the sand, the finds are concentrated in two regions separated by a zone of lower concentration. This apparent grouping into two concentrations and the great similarity between the distribution in the topsoil (secondary position) and that in the sand (primary) have been investigated statistically by means of a x2 distribution (chi-square test) (22). This reveals that the two concentrations are in fact separate and that ploughing, which was first carried out here in depth 2 or 3 years ago, is responsible for the slight discrepancy between the two layers. There is in other words statistical support for regarding the distribution of artefacts in the two layers as a whole, allowing for slightly greater dispersal in the topsoil. As only four small fragments of polished neolithic axes have been found an no loter artefact types or secondary intrusions, the material from the topsoil and sand ’may with appropriate reservations be treated as a single cultural entity. The number of finds is small compared with other stone age settlements, nowhere exceeding 300 pieces per sq. m. From the distribution of a series of characteristic types, fig. 12-15, it is possible to define the settlement proper. If the maximum extent of each type is plotted on a single plan, a number of polygons are obtained which are basically uniform, fig. 16. The centre of gravity of each distribution has been calculated, fig. 17, and is found in every case to lie less than 1 m from the fireplace. This pattern is hardly fortuitous and must presumably reflect the pattern of settlement activities, which have apparently all been concentrated around the fireplace. A tempting explanation of these circumstances is that the implement distribution reflects the outline of a round or an oblong hut measuring 6 x 7 m, with a central fireplace. The entrance can have been to the southsouthwest near the presumptive lake shore, fig. 10-11. The concentration of flint waste presumably marks the spots in the settlement where flint was worked. Raw material The flint is well preserved; the fragments are sharp-edged, and not water-worn, but bear in a number of cases traces of frost fracture, both before and especially after working. The preferred material is grey-black, granular, bryozoan flint of Danian type. To permit comparison with other recently published late glacial or post-glacial finds, the material from Bro has been studied in great detail. A specification is given in the table on p. 19-20. 5,324 items of worked flint were recovered, 122 of which (2.8 %) are implements. The implements are classified in the list p. 19-20. Technique In the following, the flint technique of the Bro find will be compared with that of the boreal Maglemose settlement Stallerupholm (32). The Bro find is characterized by an irregular flaking technique. The majority of the flakes are irregularly discoid, regular discs being rare. Core technique is not represented. The blades fig. 20 are thick, long and broad with an irregular, acutely triangular shape, regular blades with parallel edges being very rare. They often have a triangular cross-section and a single keel. The average length is 7 cm and the average width 2½ cm, fig. 18 a-b. The peculiar blade form with only one longitudinal ridge suggests that they are rejected raw material for tanged points. Micro-blades are rare. Fig. 18-19 compares the Bro blades with those from Stallerupholm (32). It is apparent that the late glacial blades are longer, broader and thicker than the post-glacial ones. And whereas micro-blades comprise only about 5 % of the Bro blades, the corresponding figure for Stallerupholm is 30 %. The cores are classified in the table p. 23. The Bro find is dominated by broad, conical cores of type A, fig. 21-22, with a single platform (20 specimens). This form comprises 71 % of the total cores. The length ranges between 4½ and 8½ cm. In comparison, A-cores comprise only 50 % of the Stallerupholm total. At Bro, regular cylindrical cores of type B with two opposed platforms, fig. 23-24, were also found (4 specimens). This type is 6-11 cm long and is thus generally longer than the A-core. One specimen may be termed a micro-blade core. 4 cores exhibit three or more platforms (type C); they are characterized by great irregularity and short flaking. Core trimming flakes are classified in the table p. 25. Core tablets and edges of striking platforms are rare at Bro, 7,4 O/o while these types constitute 30 % at Stallerupholm. It is apparent that the predominant form is plunging flakes, fig. 25-26, deriving from cores of type A. This kind of flake comprises 18 % of the total at Stallerupholm, and 37 % at Bro. The conclusion of this analysis is that the waste material distinguishes late glacial material from other material just as fundamentally as proper implements do. lmplements Scrapers are common, being represented by 25 pieces. Their distribution will be apparent from fig. 13, which shows that they are found especially in the peripheral areas. The diagram fig. 27 shows that the scraper angle is generally more acute than, for example, that of mesolithic scrapers. Simple flake scrapers are common, fig. 28-29, a few of them being lateral-retouched flakes, fig. 30-31. Broad carinate scrapers are likewise known, fig. 32, but the commonest form has a shoulder or nose, fig. 33-38. Broken edges from this type are also known, fig. 39-40. Simple blade scrapers are rare, fig. 41. Only one double-scraper was found, fig. 42. Only one awl has been found, fig. 43. Burins are the dominating tool in the Bro find, with 37 specimens. This form is concentrated in the central part of the excavation area, fig. 14, and the distribution of scrapers and burins is mutually exclusive. 9 dihedral burins are known, five of which have the edge in the long axis of the flake, fig. 44-46. One burin has been fashioned on a tanged point, fig. 44. Three dihedral burins are formed on cores or irregular flakes, fig. 46. The commonest type of burin is the angle burin, represented by 19 specimens. Seven of these are simple burins with the facet on a break, fig. 52-54, while six have been fashioned by two burin blows, fig. 47-51. One angle burin has been formed on an oblique truncation, fig. 55. 3 plane burins were found, fig. 56. Transverse burins are represented by 11 specimens, four of which are formed on regular blades, fig. 57-58, while the other seven are formed on crude irregular flakes, where one of the facets of the back has been employed, fig. 60-62. 12 burin chips are present, two of which are from transverse burins, fig. 63-64, and the remainder from dihedral and angle burins, fig. 65. 1 burin is of indeterminate form, fig. 2. It is made on a tanged point, but cannot be classified on account of its fragmentary nature. Tanged points of Bromme-Lyngby type are represented by 7 specimens, one of which is the previously mentioned piece, which provided the impetus for the excavation, fig. 1 and fig. 66-71. The distribution of this type, which seems to be confined to the northern part of the excavation, is shown in fig. 15. The specimen fig. 66 is worthy of special attention, its percussion bulb having been removed with a series of small, secondary blows in the long axis. One shouldered point is known, fig. 72. This is probably an unfinished tanged point. The material also contains a single blade with oblique truncation. This specimen, which is unique in the Bro find, is irregular and haphazard in appearance. 14 specimens with regular, continuous, longitudinal edge retouch were recovered, twelve of which were blades and two flakes, fig. 73-74. In all cases only one edge is retouched, and only partially. Eight specimens are retouched on the right, and six on the left edge. 7 notched flakes are present, six of them with only one notch. 3 denticulated flakes were found, the toothed portion comprising two notches close together, fig. 75. Notched blades are represented by 11 specimens, all of them with only one notch, in three cases in the left edge, in six in the right and in two in the distal end. 4 denticulated blades were found. Only 3 notched blades with continuous edge retouch were found. 1 sidescraper was found, fig. 76. Summary of characteristics The Bro find represents an industry based on long, broad and thick blades of triangular cross-section. Micro-blades are rare. Core technique is unknown, and regular flakes are rare. Short conical cores of type A predominate, but longer cylindrical cores also occur. Plunging flakes dominate the swarf. Scrapers constitute 20.1 % of the tool inventory, and may be classified as simple scrapers 7 .2 %, scrapers with shoulder or rostrum 6.4 % and carinate scrapers 3.2 %. Burins comprise 31.5 % of the total implements, angle burins being the commonest type with 15.3 % of the total, while dihedral and transverse burins comprise 7 .2 % and 8.8 %. Tanged points comprise 5.6 % of the tool inventory. Denticulated flakes and blades are rare and constitute 2.5 % and 3.3 % of the implements. Notched flakes and blades are more common, with 5.8 % and 9.1 %. Flakes and blades with continuous edge retouch comprise 1. 7 % and 10 % of the artefacts. Cultural allocating and dating The Bro find must be linked with the Bromme Culture, as this is defined and described in North European literature (79-81). A typological comparison between the Bro material and the previously published settlements of Bromme (79) and Segebro (80) reveals considerable similarities -not only in the broad, fundamental features, but in many characteristic details. The technique, waste material and core types are the same at all three settlements. The implement inventory is simple and dominated by burins, scrapers and tanged points in the order given. At Bro, these three categories comprise 31.5 %, 20 % and 5 % respectively, while the corresponding values for Segebro are 18.5 %, 20 % and 7.5 % and for Bromme (lower, black layer) 43 %, 20 % and 14 % (91). The Bro find seems to occupy a position between Bromme and Segebro with respect to the relation between the groups of tools. If the types at the three settlements are evaluated individually, however, certain differences can be observed, angle burins predominating within the burin group at Bro and Segebro, while dihedral burins dominate at Bromme. Transverse burins are likewise a dominant element at Bro and Segebro, while the type is unknown at Bromme. The relation between the burin and the scraper group also differs at the three sites. The relative frequency of burins and scrapers is 2:1 at Bromme, 3:2 at Segebro and 1:1 at Bro. The percentage of burins in the entire implement inventory is also considerably smaller at Bro and Segebro than at Bromme. The percentage contribution of tanged points to the whole tool inventory at Bromme is three times as great as at Bro and twice as great as at Segebro. Dating The complete lack of charcoal in the find and the lack of a pollen analysis prevent a scientific dating of the Bro settlement. Attempts at dating have to rely on purely archaeological-typological and geological-stratigraphical evidence. The close typological similarity between Bro and Segebro (and Bromme) indicates that the two settlements must be of the same age. Bromme has been dated by pollen analysis to an unspecified part of the Allerød period (111), which had a duration of 700 years (112). From geological evidence, Segebro may be dated only within the general framework of Allerød and younger Dryas (113). Assuming that these datings are correct, Bro may be assigned to the same framework, of Allerød and younger Dryas. The question is, whether it is possible to narrow this rather crude dating down. Since a considerable part of the material was frost-fractured before, but especially after manufacture, the settlement must have been inhabited during a cold period, continuing after the site had been abandoned. Since no traces of a humus surface have been found at either Bro or Segebro, which would be expected if the settlements had been inhabited in the Allerød period (and as is known at Bromme), Bro and Segebro must have been inhabited at a time when the vegetation cover was too sparse to form humus. All these indications seem to point to the younger Dryas, presumably an early phase. The geological dating of the Bro find to the younger Dryas suggests that the Bromme Culture extends into that period. The palynological dating of the well-known tanged arrowhead from Nr. Lyngby (120) points in the same direction. This dating also accords with the typological placing of the find, where a low frequency of burins in relation to scrapers, and the dominance of angle and transverse burins in relation to dihedral burins point to the younger Dryas. At both Stellmoor II and Deimern 45 (124), which are dated to the younger Dryas, the burin group is characterized by angle and transverse burins. The conclusion is that Bro must be allocated to the younger Dryas. In a North European context, Bro and Segebro seem to occupy a typological position between Bromme and Stellmoor II/Deimern 45. In the South Scandinavian context, Bro seems to occupy a place between Bromme and Segebro. The still very rare published late glacial settlements of Southern Scandinavia thus seem to form a chronological series exhibiting a gradual typological development within and between the individual groups of implements. The geological and the typological dating of Bro thus seem to be in accordance, both pointing to an early phase of the younger Dryas. Settlement type Bro and Segebro are of the same size, situation and exactly the same implement inventory. This suggests that they both represent the same type of settlement, presumably an occupation by one social entity (family) for a single short period (seasonal settlement); the absence of animal bones prevents the establishment of the season, however. The outline of the huts, if they are such, is difficult to determine, but has presumably been oblong-oval or round. Søren Andersen